Development of antiferromagnetic Heusler alloys for the replacement of iridium as a critically raw material. (27th September 2017) - Hirohata, Atsufumi; Huminiuc, Teodor; Sinclair, John; Wu, Haokaifeng; Samiepour, Marjan; Vallejo-Fernandez, Gonzalo; O'Grady, Kevin; Balluf, Jan; Meinert, Markus; Reiss, Günter; Simon, Eszter; Khmelevskyi, Sergii; et al.
Abstract: As a platinum group metal, iridium (Ir) is the scarcest element on the earth but it has been widely used as an antiferromagnetic layer in magnetic recording, crucibles and spark plugs due to its high melting point. In magnetic recording, antiferromagnetic layers have been used to pin its neighbouring ferromagnetic layer in a spin-valve read head in a hard disk drive for example. Recently, antiferromagnetic layers have also been found to induce a spin-polarised electrical current. In these devices, the most commonly used antiferromagnet is an Ir–Mn alloy because of its corrosion resistance and the reliable magnetic pinning of adjacent ferromagnetic layers. It is therefore crucial to explore new antiferromagnetic materials without critical raw materials. In this review, recent research on new antiferromagnetic Heusler alloys and their exchange interactions along the plane normal is discussed. These new antiferromagnets are characterised by very sensitive magnetic and electrical measurement techniques recently developed to determine their characteristic temperatures together with atomic structural analysis. Mn-based alloys and compounds are found to be most promising based on their robustness against atomic disordering and large pinning strength up to 1.4 kOe, which is comparable with that for Ir–Mn. The search for new antiferromagnetic films and their characterisation are useful for further miniaturisation and development of spintronic devices in a sustainable manner.